Community Empowerment in Providing Local Supplementary Feeding for Pregnant Women With CED at Puskesmas Bengkuring, Samarinda - Sari, Rika Yunita; Ariani, Preati Ayu; K, Iriyani; Wisnuwardani, Ratih Wirapuspita (Jurnal Abdimas, 2025)
Chronic Energy Deficiency (CED) in pregnant women remains a pressing nutritional issue in Indonesia, particularly in Samarinda City. This community program aimed to improve the nutritional status of pregnant women with or at risk of CED through the provision of local food-based supplementary feeding (PMT) and the empowerment of community health cadres. The intervention took place at Bengkuring Health Center from April to December 2024, targeting 40 pregnant women. Activities included cadre training, preparation of nutritious local meals, and monitoring of Body Mass Index (BMI) before and after the intervention. Results indicated a significant increase in average BMI (p < 0.05), although the duration of PMT was not significantly associated with BMI improvement. The program successfully engaged the community in health-focused food preparation and raised awareness among pregnant women about the importance of maternal nutrition. These findings support the effectiveness of local PMT as a tool for both nutritional intervention and sustainable community empowerment. In the long term, such initiatives can help reduce the prevalence of CED and contribute to healthier pregnancy outcomes. Continued collaboration across sectors is essential to ensure the sustainability of this program.